Lost Plays in Shakespeare's England
XIII, 295 p.
Keywords: Lost Plays in Shakespeare's England examines assumptions about what a lost play is and how it can be talked about; how lost plays can be reconstructed, particularly when they use narratives already familiar to playgoers; and how lost plays can force us to reassess extant plays, particularly through ideas of repertory studies.